DEVELOPMENT STRATEGY FOR BUNDA LISA'S MILK CAKE UMKM IN DEWANTARA DISTRICT, NORTH ACEH REGENCY - Muhammad Zaihabi; Setia Budi; Eva Wardah (Jurnal Mahasiswa Agribisnis, 2026)
This study aims to identify the development strategy of the Bolu Susu Bunda Lisa Micro, Small, and Medium Enterprise (UMKM) using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The method used in this study was a qualitative approach using interviews and direct observation at the business location. The results indicate that the Bolu Susu Bunda Lisa UMKM possesses key strengths, including the experience of the business owner, affordable product prices, and a strategic location. However, this business also faces weaknesses, including unstable production and limited capital. From an external analysis, opportunities exist that can be exploited, such as increasing public interest in local traditional cakes and the application of technology for production efficiency. On the other hand, threats include rising raw material prices and a lack of government support.  Based on the SWOT analysis, several development strategies were formulated, including developing a distribution system through collaboration with travel drivers and establishing a reseller network from the local community. This research is expected to contribute to the development of UMKM in North Aceh and serve as a reference for further research.